Havens and Hazards: Exploring the Critical Role Toronto Public Libraries Play in Serving the Precariously Housed - Davis, Jackson; Heintzman, Isobel; Mehta, Aditi (International Journal on Homelessness, 2026)
This article explores the dynamics of socio-spatial exclusion in Toronto, focusing on public libraries as critical safe spaces for people experiencing homelessness and those that are precariously housed. Employing a framework of ‘havens’ and ‘hazards,’ we illustrate the ways in which urban environments communicate attitudes towards homelessness, influencing how vulnerable populations navigate these spaces. We argue that exclusionary measures (hazards) guide vulnerable populations to seek refuge in Toronto libraries, one of the few remaining urban public spaces offering free access, services, and respite (havens). This phenomenon is exaggerated by a lack of haven locations across Toronto and an increase in hazards in our case study area which we depict cartographically and photographically. Anchoring our case study at the Toronto Public Library's (TPL) Spadina Road Branch, we illustrate how branches offer services beyond traditional library functions in assisting vulnerable patrons. Branch staff and TPL management are actively engaged in community outreach, providing tailored programs and bridging service gaps through referrals and partnerships with social organizations. Key initiatives include establishing a TPL system-wide social worker, a mobile trauma-informed crisis and de-escalation team, as well as compassionate staff accommodating the unique needs of vulnerable patrons. However, the study exposes a discrepancy between TPL’s intended trauma-informed safety policies regarding security guards and law enforcement. Regressive securitization tactics undermine the library as a haven, thereby impacting the efficacy of its broader safety and inclusion framework. We advocate for a reassessment of library security measures and broader integration of social services in library branches to enhance the safety for all community members.